Sample Size Calculation in Oncology Trials: Quality of Reporting and Implications for Clinical Cancer Research. (December 2015) - Bariani, Giovanni M.; de Celis Ferrari, Anezka C.R.; Precivale, Maristela; Arai, Roberto; Saad, Everardo D.; Riechelmann, Rachel P.
Abstract : Objectives: Sample size calculation (SSC) is a pivotal step in clinical trial conception and design. Herein, we describe the frequency with which oncology phase III trials report the parameters required for SSC. Materials and Methods: We systematically searched for phase III trials published in 6 leading journals, which were accompanied by editorials from January 2008 to October 2011. Two blinded investigators extracted required and optional parameters for SSC according to the primary endpoint. Results: We retrieved 140 eligible phase III trials. The median target sample size was 596 subjects (50 to 40, 000); in 66.4% of cases, the number of enrolled subjects was at least 90% of the target. The primary endpoint was a continuous variable in 5.7%, categorical in 30.0%, and a time-to-event variable in 64.3% of phase III trials. Although nearly 80% reported a target sample size, only 27.9% of the trials provided all the required parameters for proper SSC. The most commonly reported parameters for sample size computation were α (93.6%) and β (90.7%) errors. The parameters least reported were the expected outcomes in the control or experimental groups, each provided in only 57.9% of trials. Conclusions: The quality of SSC reporting in phase III cancer trials is poor. Such incomplete reporting may compromise future study designs, pooling of data, and interpretation of results. Lack of transparency in SSC reporting may also have ethical implications.